Financial Report Integrity of Banking Companies on the Indonesian Stock Exchange from 2020 to 2023 - Gusti, Kanaya Pinaring (TEMA, 2025)
This study aims to empirically examine the effect of leverage, profitability, financial distress, audit quality, and institutional ownership on the integrity of financial statements of banking companies listed on the Indonesian Stock Exchange (IDX) during 2020–2023. Using a quantitative approach, this research employs secondary data obtained from the companies’ annual reports published on the official IDX website and collected through documentation. A total of 164 observations were selected using the purposive sampling method and analyzed through multiple linear regression. The findings reveal that profitability significantly affects the integrity of financial statements, as it influences the transparency of financial information. However, leverage, financial distress, audit quality, and institutional ownership are found to have no significant effect on financial statement integrity, possibly because companies experiencing high leverage and financial distress tend to adopt conservative accounting practices to maintain public trust.